Упростить 18x^-6/y^5*7y^-5/6x^-12

коаладоби коаладоби    3   16.12.2020 18:01    4

Ответы
илюха190 илюха190  15.01.2021 18:02

3х^(6)/7

Объяснение:

18x^(-6) / y^(5) * 7y^(-5) / 6x^(-12) = 18x^(-6) / y^(5) * 7y^(-5) * 1/ 6x^(-12) = 18x^(-6) * 1 / y^(5) * 7y^(-5) * 6x^(-12) = 3x^(6) / y^(5) * 7y^(-5) = 3х^(6)/7

ПОКАЗАТЬ ОТВЕТЫ
VovanBah VovanBah  15.01.2021 18:02

21

х^18 y^10

Объяснение:

18x^-6 7y

× : 6x^-12=

y^5 6

3x^-6

× 7y^-5 x^-12=

y^10

21x^-18. 21

=

y^10. x^18 y^10

ПОКАЗАТЬ ОТВЕТЫ